1983
DOI: 10.1111/j.1365-2125.1983.tb02119.x
|View full text |Cite
|
Sign up to set email alerts
|

Dazoxiben, a thromboxane synthetase inhibitor, in the treatment of Raynaud's syndrome: a double‐blind trial.

Abstract: 1 UK-37248 (dazoxiben), an orally active thromboxane synthetase inhibitor, was evaluated in a double-blind trial of patients with severe Raynaud's syndrome. 2 Twenty patients were enrolled in the study. Eleven of these patients received dazoxiben 400 mg day and nine received matching placebo capsules. Treatment was given for 6 weeks and the patients reviewed at 2 weekly intervals during the study. 3 Assessment of response was judged by clinical symptoms and hand temperature measurements. Haematological and hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Nevertheless, 12 weeks' treatment with dazoxiben did not produce significant changes in finger-skin temperature, capillary blood cell velocity or in the duration or severity of attacks of Raynaud's phenomenon. These findings are similar to those reported from a 6-week study of patients with Raynaud's phenomenon taking dazoxiben in which there was no significant increase in hand temperature [8]. However, in their study there was an apparent reduction in frequency of Raynaud's attacks.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, 12 weeks' treatment with dazoxiben did not produce significant changes in finger-skin temperature, capillary blood cell velocity or in the duration or severity of attacks of Raynaud's phenomenon. These findings are similar to those reported from a 6-week study of patients with Raynaud's phenomenon taking dazoxiben in which there was no significant increase in hand temperature [8]. However, in their study there was an apparent reduction in frequency of Raynaud's attacks.…”
Section: Discussionsupporting
confidence: 89%
“…In a number of these diseases, the balance between TxA 2 and prostacyclin is altered, leading to excessive vasoconstriction and hemostatic disorders. Indeed, in patients with primary vascular diseases involving excessive vasoconstriction, such as migraine headache (43), primary pulmonary HT (22), and Raynaud's disease (68), TxA 2 production is elevated, and the TxS inhibitors CGS-13080 and dazoxiben have been used successfully in the treatment of the latter two diseases (7,66). Findings from animal studies support the proposed relationship between TxA 2 and the development of these diseases (14,26).…”
Section: The Role Of Txa 2 In CV Homeostasis: Historical Viewpointmentioning
confidence: 74%
“…Animal studies have also revealed a similar relationship between TxA 2 and excessive pulmonary vasoconstriction (11,22). Furthermore, TxS inhibitors such as CGS-13080 and Daz have been used successfully in the treatment of PPH and Raynaud's Disease (7,65).…”
Section: Clinical Significance Of the Present Findingsmentioning
confidence: 96%